Anomalous carbon uptake in Australia as seen by GOSAT. Issue 19 (5th October 2015) - Detmers, R. G.; Hasekamp, O.; Aben, I.; Houweling, S.; van Leeuwen, T. T.; Butz, A.; Landgraf, J.; Köhler, P.; Guanter, L.; Poulter, B.
Abstract One of the unanswered questions of climate change is how the biospheric uptake of carbon responds to events such as droughts and floods. Especially, semiarid regions have received interest recently, as they can respond very rapidly to changing environmental conditions. Here we report on a large enhanced carbon sink over Australia from the end of 2010 to early 2012 detected using the Greenhouse Gases Observing SATellite (GOSAT). This enhanced sink coincides with the strong La Niña episode, accompanied by record‐breaking amounts of precipitation. This precipitation led to an enhanced growth of vegetation, resulting in large increases in biospheric carbon uptake in line with increased levels of vegetation fluorescence. An inversion based on the satellite retrievals confirms this strong anomaly in the sink of roughly 0.77 ± 0.10 Pg C yr−1 or 1.5 ± 0.2 Pg C in total for the April 2010 to December 2011 period, which corresponds to 25% of the multiyear annual average gross primary production of the Australian biosphere.